Neurological involvement in patients with systemic autoimmune rheumatic diseases: a descriptive study in an Egyptian cohort - Doaa Hassan Sayed Attia; Alshaimaa Aboul Fotouh; Reem Hamdy Abdellatif Mohammed (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Neurologic manifestations in the systemic autoimmune rheumatic diseases (SARDs) are protean. They add to the disease burden and could contribute to mortality. Increasing awareness about the neuro-rheumatologic syndromes might help with early diagnosis and effective therapy. Our aim is to survey the clinical and imaging patterns of neurological involvement in Egyptian patients with SARDs. Results Neurological involvement is common in Behçet’s disease (BD) (12.7%) and systemic lupus erythematosus (SLE) (6.4%) patients compared with other SARDs. Compared with SLE, neurological involvement in BD tends to develop at an older age (31 ± 7.1 versus 28.3 ± 9.6 years = 0.022) with a greater progression risk (13.8% versus 2.6%, P = 0.003). A higher proportion of SLE patients had abnormal neuroimaging without neurological symptoms (15.7% versus 4.3%, P = 0.026, OR = 4.9, 95%CI 1.1–22.4). SLE patients had a higher frequency of seizures (31.3% versus 6.4%, P < 0.001, OR = 6.7, 95%CI 2.7–16.7) and benign intracranial hypertension (9.6% versus 1.1%, P = 0.009, OR = 9.8, 95%CI 1.2–77.7) but a lower prevalence of quadriplegia due to brain insult (1.7% versus 3.2%, P = 0.045, OR = 0.2, 95%CI 0.04–0.9), dural sinus thrombosis (13% versus 33%, P = 0.001, OR = 0.3, 95%CI 0.2–0.6), brainstem syndrome (0.9% versus 6.4%, P = 0.047, OR = 0.1, 95%CI 0–1.1) and cranial neuropathies (9.6% versus 31.9%, P < 0.001, OR = 0.2, 95%CI 0.1–0.5). Concerning neuroimaging, brain atrophic changes were more common (27.4% versus 9.5%, P = 0.002, OR = 3.6, 95%CI 1.6–8.3) while thrombosis was less prevalent (36.3% versus 53.6%, P = 0.016, OR 0.5, 95%CI = 0.3–0.9) in lupus patients. The cerebral cortex was more commonly affected (20.4 versus 4.8%, P = 0.002, OR = 5.1, 95%CI 1.7–15.4) while dural sinuses (14.2% versus 40.5%, P < 0.001, OR = 0.2, 95%CI 0.1–0.5), basal ganglia (1.8% versus 10.7%, P = 0.010, OR = 0.2, 95%CI 0–0.7), diencephalon (0% versus 13.1%, P < 0.001) and brainstem (1.8% versus 22.6%, P < 0.001, OR = 0.1, 95%CI 0–0.3) were less frequently involved in SLE patients. Concerning other SARDs, cranial neuropathies were the most common neurological presentations. Abnormalities in neuroimaging did not correlate with the patients’ clinical presentations. Conclusions Neurological presentations associated with SARDs are protean. Neuroimaging abnormalities should be interpreted within the context of the clinical picture and the results of other investigations.